2019
DOI: 10.12659/msm.913684
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Propensity Score Matched Study of the Preoperative C-Reactive Protein to Albumin Ratio and Prognosis in Patients with Resectable Non-Metastatic Breast Cancer

Abstract: Background A retrospective study aimed to investigate the association between the CRP to albumin ratio and prognosis in patients with resectable non-metastatic breast cancer in terms of disease-free survival (DFS) and overall survival (OS) using propensity score matching. Material/Methods Patients with newly diagnosed resectable non-metastatic breast cancer (n=200) who underwent modified radical mastectomy between January 2008 to June 2013 included a group with an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…One study by Zhou L showed that 200 patients with non-metastatic breast cancer receiving modified radical mastectomy used the CAR to predict the prognosis, and CAR was significantly associated with reduced DFS and OS, and proved that an increased CRP to albumin ratio was an independent risk factor for long-term outcome and predicted reduced DFS and OS. 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study by Zhou L showed that 200 patients with non-metastatic breast cancer receiving modified radical mastectomy used the CAR to predict the prognosis, and CAR was significantly associated with reduced DFS and OS, and proved that an increased CRP to albumin ratio was an independent risk factor for long-term outcome and predicted reduced DFS and OS. 31 …”
Section: Discussionmentioning
confidence: 99%
“…One study by Zhou L showed that 200 patients with non-metastatic breast cancer receiving modified radical mastectomy used the CAR to predict the prognosis, and CAR was significantly associated with reduced DFS and OS, and proved that an increased CRP to albumin ratio was an independent risk factor for long-term outcome and predicted reduced DFS and OS. 31 Yubo Liu's study found that patients with high CRP/ Alb had poor overall survival compared to those with low CRP/Alb, and CRP/Alb was an independent prognostic factor for overall survival. 32 Endocrine therapy represents an important strategy in the management of hormone positive breast cancer.…”
Section: Dovepressmentioning
confidence: 99%
“…CAR was initially assessed in patients with acute diseases and sepsis. 81 , 82 Recently, its prognostic value has gained importance in cancers including hepatocellular carcinoma, 83 gastric cancer, 84 and esophageal squamous cell carcinoma, 85 as well as ovarian, 86 breast, 87 and cervical cancers. 87 Elevated preoperative CAR levels are thought to be associated with poor survival of patients with these tumor types.…”
Section: Inflammatory Markersmentioning
confidence: 99%
“… 81 , 82 Recently, its prognostic value has gained importance in cancers including hepatocellular carcinoma, 83 gastric cancer, 84 and esophageal squamous cell carcinoma, 85 as well as ovarian, 86 breast, 87 and cervical cancers. 87 Elevated preoperative CAR levels are thought to be associated with poor survival of patients with these tumor types. Moreover, the CAR index may serve as a prognostic biomarker of cardiotoxicity during anti-cancer therapy.…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…In addition, the prognostic value of CRP kinetics, dynamic change of CRP level throughout treatment, has been con rmed in metastatic nasopharyngeal carcinoma and renal cell carcinoma [27][28][29]. Furthermore, a novel prognostic markers involving in ammation and nutrition, CRP to albumin ratio (CAR), has been evaluated in colorectal cancer, liver cell carcinoma, lung cancer, and other solid tumors [30][31][32][33][34]. The prognostic signi cance of CRP level, CRP kinetics and CAR in B-iNHL are unclear.…”
Section: Introductionmentioning
confidence: 99%